TYPES OF PROPERTY IN THE ARMED FORCES OF UKRAINE - Novikova, Ye. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article analyzes types of property in the Armed Forces of Ukraine and considers several options for its division. Contradictions between the Laws of Ukraine "On the Legal Regime of Property in the Armed Forces of Ukraine" and "On Economic Activity in the Armed Forces of Ukraine" were established, that make it possible to assume the presence of property other than military in the Armed Forces of Ukraine, and ways to eliminate it were proposed. Taking into an account the possibility of military units to carry out economic activity, property in the economic sector was separated from military property and classified in accordance with Art. 139 of the Commercial Code of Ukraine. The definitions of "economic activity" reflected in the Commercial Code of Ukraine, the Law of Ukraine "On Economic Activity in the Armed Forces of Ukraine" and the Regulation on the military (ship) economy of the Armed Forces of Ukraine, approved by the Order of the Ministry of Defense of Ukraine dated 16.07.1997 № 300, are compared. It is justified that the economic activity of the Armed Forces of Ukraine must be understood in the sense given by the Commercial Code of Ukraine and the Law of Ukraine "On Economic Activity in the Armed Forces of Ukraine". At the same time, the Regulation should be altered: firstly, by excluding of the alternative definition of the organization and management of military (ship) economy – the phrase "economic activity"; secondly, by defining an organization and management of the military (ship) economy as an activity of authorized entities, the main tasks of which are comprehensive and permanent providing of combat training and mobilization readiness of military units and formations, creation of conditions for their rapid transition from peaceful state to martial law. It was established that the definitions of military property and military (ship) economy are identical, and therefore the division of military (ship) economy is applicable to military property. The classification of property in the Armed Forces of Ukraine according to the sources of its acquisition is proposed.
Keywords: military property, property in the Armed Forces of Ukraine, military (ship) economy, economic activity, legal regime of property